'Not suitable for exhibition': Cinema Censorship and International Intervention in Argentina, 1939–1945. (2nd January 2022) - Mizala, Camila Gatica
Abstract : During the Second World War, Buenos Aires's Government censored a number of films that they viewed as potentially having a detrimental effect on the political outlooks of its people of Buenos Aires. These bans, which were later extended to the whole nation, were due to the intervention of international and local politicians and diplomats in an attempt to influence the citizens' opinion of the Axis powers. Films such as Confessions of a Nazi Spy (1939) and The Great Dictator (1940) were only screened once the war was over. Through specialized cinema magazines published in Buenos Aires, this article problematizes the different geographical scales in which censorship took place in Argentina during the Second World War. Moreover, it discusses the reasoning and discourses of culture and morality as the main ideas behind the censorship of these films in Buenos Aires, and Argentina more generally.